Digital Transformation in Business (theory/practice) - Bayrak Meydanoglu, Ela Sibel (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2020)
Augmented Reality. Mobile Marketing. New Role of HR. Blockchains. Legal Business. Monitoring Corporate Reputation. Controlling. Digital Maturity Models for SMEs. Social Sustainability. Robo-Advisors vs. Human Financial Advisors